Pengantin Pesanan di Dunia Maya Sebagai Kejahatan Transnasional: Eksploitasi Seksual dan Upaya Penegakan Hukum - Wabilia Husnah (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2022)
As a transnational crime, the mail-order brides are evolving into a form of cyber-trafficking. The mail-order brides websites advertise Indonesian women to be traded as Chinese men's wives. This paper aims to analyze the eradication of the transnational crime, by revealing the sexual exploitation in it, root of the problem, and law enforcement against cyber-trafficking. This is qualitative research with a case study approach to three mail-order brides websites. By using the theory of Radical Feminism, this study finds women are victims of sexual exploitation, caused by patriarchal system in the culture of two countries. There are several international and national legal instruments that regulate human trafficking, although does not explicitly regulate the elements of cyber-trafficking with the mail-order bride website mode. Therefore, to eradicate the transnational crime, it is necessary to improve legal instruments, and dismantle the patriarchal system as the root causes of the mail-order bride website.